Performance Analysis of a Double-effect Adsorption Refrigeration Cycle with a Silica Gel/Water Working Pair - Atsushi Akisawa; Takahiko Miyazaki; Yuki Ueda; Marlinda; Aep Saepul Uyun (Energies, 2010)
A numerical investigation of the double-effect adsorption refrigeration cycle is examined in this manuscript. The proposed cycle is based on the cascading adsorption cycle, where condensation heat that is produced in the top cycle is utilized as the driving heat source for the bottom cycle. The results show that the double-effect cycle produces a higher coefficient of performance (COP) as compared to that of the conventional single-stage cycle for driving temperatures between 100 °C and 150 °C in which the average cycle chilled water temperature is fixed at 9 °C. Moreover, the COP of the double-effect cycle is more than twice that of the single-stage cycle when the temperature reaches 130 °C. It is also observed that the adsorbent mass ratio of the high temperature cycle (HTC) to the low temperature cycle (LTC) affects the performance of the double-effect adsorption refrigeration cycle.